Research participant understanding and engagement in an institutional, self‐consent biobank model. Issue 1 (20th September 2020) - Schmanski, Andrew; Roberts, Emily; Coors, Marilyn; Wicks, Stephen J.; Arbet, Jaron; Weber, Rachel; Crooks, Kristy; Barnes, Kathleen C.; Taylor, Matthew R. G.
Abstract: The number of institutional and governmental biobanks and the target enrollment sizes of modern biobanks are increasing, affording more opportunities for the public to participate in biobanking efforts. In parallel with these expansions are pressures to increase the efficiency of obtaining informed consent using shorter consent forms that cover a broader scope of research and increasingly include provisions for return of research or clinical genetic test results to participants. Given these changes, how well these participants understand genetics, their level of understanding of what they are consenting to, and their wishes to engage longitudinally and receive biobank results are not well understood. We surveyed participants in a large, medical system‐based biobank who had enrolled through a two‐page, self‐consent process about their baseline knowledge of genetics, understanding and recall of the consent process, wishes for future contact and engagement, and level of interest in receiving clinical genetic testing results. A total of 856 consented persons participated in the survey (67% women; 67% white). Participants' general reported genetics knowledge was relatively high (mean 11.60 of 15 questions answered correctly) as was recall of key elements from the two‐page consent form. Overall participant enthusiasm for future contact by the biobank and for receiving clinical genetic testing results was high. The use of a two‐page, self‐consent process in a large, institutional biobank resulted in high levels of consent recall and enthusiasm for future ongoing engagement and receipt of genetic testing results by participants. Abstract :